ANALISIS BIBLIOMETRIK PADA PENGARUH BERITA DI MEDIA SOSIAL TERHADAP PERILAKU REMAJA DI LINGKUNGAN MASYARAKAT - Putri, Adelia Kharisma (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2021)
Adolescence is an age that is usually used to find one's identity. At the age of teenagers, it is not surprising that many young people whose behavior is sometimes influenced by the atmosphere of the environment, both from friends and family. This influence is very strong concerning adolescents, especially in terms of conveying information. At the age of teenagers, most young people like to find news information that is being hotly discussed through their respective social media. So, it is undeniable that teenagers can know many things just by holding a cellphone. However, in this case, it must be underlined that many teenagers receive invalid news information so that fake news or hoax news often occur which will affect the condition of teenagers in responding to a problem in the community. The purpose of this study is to identify and analyze the behavior of adolescents in receiving and understanding the news that is spread on social media in the surrounding environment. So, in this study, the author uses the Bibliometric Technique which in the process uses a set of articles or journals as a reference for research sources. The article or journal is obtained through Google Scholar as the main channel in finding analytical reference sources. Then the results of the analysis are visualized and explained in detail through theoretical dialogue and the results of bibliometric analysis. Keyword: bibliometric, social media, behavior, adolescent